Red Desaturation Prevalence and Severity in Healthy Patients. Issue 1 (February 2022) - Mikolajczyk, Brian; Ritter, Andrew; Larson, Christian; Connett, John; Olson, Joshua; McClelland, Collin; Lee, Michael S.
Abstract : Background and Objectives: To determine the percentage of the healthy population that responds asymmetrically to the red desaturation test and to approximate the degree of red desaturation in those individuals. We also sought to elucidate any correlation between demographic variables and red desaturation prevalence and severity. Methods: Adults aged 18 years and older with a normal eye examination, including confrontation fields and best-corrected visual acuity of ≥20/25 in both eyes, were eligible for this prevalence study. Those with objective or subjective afferent visual dysfunction were excluded. A total of 101 eligible participants (68.3% female and 31.7% male; racial/ethnic breakdown of 77.2% White, 11.9% Black, 8.9% Asian, 2.0% N/A; mean (SD) age: 41.5 (15.3) years) were queried whether the monocular perception of redness of a standardized tropicamide bottle cap was the same and to estimate the interocular percentage difference, with 1 eye perceiving the bottle cap at "100% redness." Results: Twenty-four participants (23.8%) experienced some degree of red desaturation. For these individuals with red desaturation, the average interocular difference was 9.0% (range 2%–25%, 95% confidence interval 6.0%–12.0%). There was no statistical evidence for a relationship between red desaturation and race, sex, or age. Discussion: This study shows that nearly a quarter of healthy patients without apparent optic nerve or macular dysfunction may recognize red desaturation. This deserves consideration when interpreting red desaturation testing in patients suspected to have unilateral optic neuropathy. Further research with larger sample sizes may identify predictors of red desaturation in healthy patients, establish the red desaturation threshold separating pathologic from physiologic phenomena, and assess the repeatability of red desaturation over time in affected individuals.